Modeling and assessing of sustainable supply chain finance:A case study of practioners and academician in Malawian - Kishombe, Nellie; Malin, Ma Lin (International Journal of Scientific Research and Management (IJSRM), 2022)
All over the world, the concept of Supply Chain Finance has emerged through the globalization of trade. The common sense within a supply chain is that suppliers are trying to receive their payments as early as possible while buyers are increasing their payment terms. SCF attempts to cope with this problem and creates opportunities for all parties creating a ‘win–win’ situation for both buyer and supplier by giving the buyer the opportunity to extend payment terms and pay the supplier in advance. This process allows all parties to free up operating working capital and provide financing in favor of the supplier. With the development of Supply Chain Management, two approaches gained the most recognition; Working Capital Management and Supply Chain Finance. Both are considered drivers for a financially stable supply chain. A Supply Chain. This thesis aims to provide a single definition by reviewing the theory of Supply Chain Finance and provide the reader with an implementation checklist and its benefits of it. The theory will then be backed up by expert interviews.